Educação ambiental: um estudo das concepções e atitudes dos educadores da educação infantil em uma escola do município de Castanhal - OLIVEIRA, Roseane dos Santos (2020)
This work presents a brief bibliographical survey, application of a questionnaire (appendix) and interview to the teachers of Early Childhood Education. It discusses the importance of work with the theme Environmental Education in early childhood education. It tries to identify how the theme has been treated in a School of Early Childhood Education in the municipality of Castanhal. It discusses the importance of preserving the environment and raising awareness in children so that they live with quality of life, as an essential prerequisite for good health for today and tomorrow. As this subject is important for the development of children, the work intends to show teachers the importance of developing this theme in early childhood education, participation in the formation of children's autonomy in relation to the environmental space and thus benefit them as future citizens